The current practice of family-centred care in Italian neonatal intensive care units: A multicentre descriptive study - Dall'Oglio, I.; Mascolo, R.; Tiozzo, E.; Portanova, A.; Fiori, M.; Gawronski, O.; Dotta, A.; Piga, S.; Offidani, C.; Alvaro, R.; Rocco, G.; Latour, Jos (Churchill Livingstone, 2018)
© 2018 Elsevier Ltd Objectives: To explore family-centred care practices in Italian neonatal intensive care units and describe areas for improvement. Methods: A cross-sectional, multicentre, survey was conducted using the Italian language version of “Advancing family-centred new-born intensive care: a self-assessment inventory”. The instrument is divided into 10 sections rating the status of family-centred care (1 = not at all, 5 = very well) and ranking the perceived priority for change/improvement (1 = low, 3 = high). A representative group of staff and parent for each unit were invited to complete the survey. Data was collected between January and June 2015. Correlations among unit characteristics and sections within the survey were explored. Settings: All Italian neonatal intensive care units (n = 105) were invited. Results: Forty-six (43.8%) units returned the survey. The “Leadership” section scored highest in status of family-centred care (mean = 3.45; SD 0.78) and scored highest in priority for change (mean = 2.44; SD 0.49). Section “Families as Advisors and Leaders” scored lowest both in status (mean = 1.66; SD 0.67) and in priority for change (mean = 2.09; SD 0.59). The number of discharged infants was positively correlated with many sections in priority for change (r 0.402–0.421; p <.01). Conclusion: This study showed a variability in the organisation of family-centred care practices in Italian neonatal intensive care units and the need to involve parents as partners in the care team. Although family-centred care is considered important by Italian neonatology healthcare professionals, much remains to be done to improve family-centred care practices in neonatal intensive care units in Italy.